Cross-Sector Networks And Social Capital In MSME Development: An Urban Sociology Study In Situbondo - Widowati, Widowati; Masruroh, Binti; Soffi, Dewi Ariyanti (Department of Sociology, Faculty of Social and Political Science, Universitas Padjadjaran, 2026)
ABSTRACT This study analyzes the role of social capital in strengthening networks and cross-sector collaboration among Micro, Small, and Medium Enterprises (MSMEs) in urban Situbondo using the framework of Pierre Bourdieu, particularly bonding, bridging, and linking social capital. A qualitative case study approach was employed, with data collected through in-depth interviews, observations, and documentation involving MSME actors and stakeholders. The findings show that MSMEs primarily rely on bonding social capital rooted in family, community, and religious ties, which supports business continuity but limits access to broader markets and resources. Bridging social capital, reflected in cross-sector collaboration, expands networks, enhances information exchange, and creates wider market opportunities. Linking social capital plays a strategic role in connecting MSMEs with formal institutions such as government and financial sectors. The novelty of this study lies in its integrative analysis of the transformation from bonding-based survival strategies to bridging and linking-oriented expansion strategies in an urban MSME context. Theoretically, this study extends Bourdieu’s concept by demonstrating the dynamic interaction of social capital forms in shaping network expansion and economic mobility.Keywords: Social Capital, MSME, Collaboration, Networks, Bourdieu ABSTRAK Studi ini menganalisis peran modal sosial dalam memperkuat jejaring dan kolaborasi lintas sektor antar Usaha Mikro, Kecil, dan Menengah (UMKM) di Situbondo perkotaan dengan menggunakan kerangka kerja Pierre Bourdieu, khususnya bonding, bridging, dan linking social capital. Pendekatan studi kasus kualitatif digunakan, dengan data yang dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi yang melibatkan pelaku UMKM dan pemangku kepentingan. Temuan menunjukkan bahwa UMKM terutama mengandalkan ikatan modal sosial yang berakar pada ikatan keluarga, komunitas, dan agama, yang mendukung kelangsungan bisnis tetapi membatasi akses ke pasar dan sumber daya yang lebih luas. Menjembatani modal sosial, tercermin dalam kolaborasi lintas sektor, memperluas jaringan, meningkatkan pertukaran informasi, dan menciptakan peluang pasar yang lebih luas. Menghubungkan modal sosial memainkan peran strategis dalam menghubungkan UMKM dengan lembaga formal seperti sektor pemerintah dan keuangan. Kebaruan dari penelitian ini terletak pada analisis integratif transformasi dari strategi bertahan hidup berbasis ikatan menjadi strategi ekspansi berorientasi jembatan dan menghubungkan dalam konteks UMKM perkotaan. Secara teoritis, penelitian ini memperluas konsep Bourdieu dengan menunjukkan interaksi dinamis bentuk modal sosial dalam membentuk perluasan jaringan dan mobilitas ekonomi.Keywords: Modal Sosial, UMKM, Kolaborasi, Jaringan, Bourdieu